Effect of Nanodisperse Carbon Fillers and Isocyanate Chain Extender on Structure and Properties of Poly(ethylene terephthalate). (20th March 2012) - Agabekov, Vladimir; Golubovich, Vera; Pesetskii, Stepan
Abstract : The effect of diisocyanate chain extender (CE) on the mechanical, rheological, and relaxation properties, as well as on molecular weight and crystallizability, of starting poly(ethylene terephthalate) (PET) and its composites containing carbon nanomaterials (CNM) such as carbon nanotubes (CNTs) and commercial carbon (CC) has been studied. The composites were compounded in molten PET using twin-screw extruder (screw diameter 35 mm; L / D = 40 ). To improve the distribution of CNM in the polymeric matrix (before introduction into the melt), they were blended with PET powder and subjected to an ultrasonic treatment in methylene chloride. The salient features of the materials structure were estimated based on DSC and relaxation spectrometry (dynamic mechanical analysis) data. It has been found that CNM additives partly suppress the PET-chain extension reactions which take place during interaction between macromolecular end groups and CE. Besides, both CNT and CC favour crystallizability of the modified PET owing to nucleation of the crystallization process. The influence of CNT appears to be more effective than that of CC. Enhancements in true mechanical strength and deformability of PET/CE/CNM composites, as against PET/CE materials, were found to be most clearly exhibited by the CNT-containing composites.